Arka Pratham: An early blooming Gladiolus cultivar - Rao, T Manjunatha; Janakiram, T; Negi, S S; Dhananjaya, M V; Kumar, Rajiv; Sujatha, S (Indian Horticulture, 2020)
Gladiolus, the queen of bulbous flowers, is commercially grown worldwide for its spike with array of colourful florets. There is an increasing demand for new cultivars which is early to bloom and has novel attractive floret colour, improved spike qualities like more number of spikes per plant, and good corm/cormel multiplication ability. As a result of several years of research during 2019, scientists at ICAR-II HR, Bengaluru have developed novel gladiolus cultivar ‘Arka Pratham’ through hybridization followed by selection for commercial cultivation. This cultivar was tested under All India Coordinated Research Project on Floriculture and recommended for agro-climatic zones 4, 5, 6 and 7. It is suitable for cut flower, bouquet preparation, floral arrangement and garden display.